Benefits of the 'village': a qualitative exploration of the patient experience of COPD in rural Australia. Issue 10 (7th October 2019) - Glenister, Kristen; Haines, Helen; Disler, Rebecca
Abstract : Objectives: This study sought to explore patients' experiences of living with, and adapting to, chronic obstructive pulmonary disease (COPD) in the rural context. Specifically, our research question was 'What are the barriers and facilitators to living with and adapting to COPD in rural Australia?' Design: Qualitative, semi-structured interviews. Conversations were recorded, transcribed verbatim and analysed using thematic analysis following the COnsolidated criteria for REporting Qualitative research guidelines. Setting: Patients with COPD, admitted to a subregional hospital in Australia were invited to participate in interviews between October and November 2016. Main outcome measures: Themes were identified that assisted with understanding of the barriers and facilitators to living with, and adapting to, COPD in the rural context. Results: Four groups of themes emerged: internal facilitators (coping strategies; knowledge of when to seek help) and external facilitators (centrality of a known doctor; health team 'going above and beyond' and social supports) and internal/external barriers to COPD self-management (loss of identity, lack of access and clear communication, sociocultural challenges), which were moderated by feelings of inclusion or isolation in the rural community or 'village'. Conclusions: Our findings suggest that community inclusion enhances patients' ability to cope and ultimately self-manage COPD. This is facilitated by living in a supportive 'village' environment, and included a central, known doctor and a healthcare team willing to go 'above and beyond'. Understanding, or supplementing, these social networks within the broader social structure may assist people to manage chronic disease, regardless of rural or metropolitan location.